9. DESAIN ULANG RESES DPRD - Abdulrahman, Wahid (Faculty of Social and Political Sciences Diponegoro University, 2014)
DPRD has significant role in conducting local administration with its three main functions which are legislating, budgeting, and controlling. To support those functions and to apply representation function, DPRD has reses period based on UU 32/2004 and 27/2009. In terms of there is no reses period guidance neither from national administration nor in DPRD rules cause the reses period in central java DPRD run less effective. Therefore a good model of reses period that could support DPAD's performance is urgently needed.